Direct conversion of sec-phosphine oxides to sec-phosphine-boranes using BH3. (16th March 2021) - Yamada, Masatoshi; Goto, Mitsutaka; Yamano, Mitsuhisa
Graphical abstract: Highlights: Direct transformation from phosphine oxide to phosphine-borane. Mild and inexpensive reaction. A wide substrate scope, the simple operation, and an interesting mechanism. Abstract: An effective and mild synthetic method for secondary phosphine-boranes from secondary phosphine oxides was developed. The slow addition of borane-tetrahydrofuran to a solution of secondary phosphine oxides at ambient temperature gave secondary phosphine-boranes with high yield. The use of air-sensitive secondary phosphines, which are common substrates for secondary phosphine-borane syntheses, is avoided in this mild process. Moreover, generation of by-products, such as secondary hydroxy-phosphine-boranes, is also minimized.